Predictive Factors for the Effect of Treatment by Noninvasive Ventilation in Patients with Respiratory Failure as a Result of Acute Exacerbation of the Chronic Obstructive Pulmonary Disease - Pejkovska, Sava (Open Access Maced J Med Sci, 2015)
BACKGROUND: Noninvasive mechanical ventilation (NIV) applies ventilator support through the patient’s upper airway using a mask. AIM: The aim of the study is to define factors that will point out an increased risk of NIV failure in patients with exacerbation of Chronic Obstructive Pulmonary Disease (COPD). PATIENTS AND METHODS: Patients over the age of 40, treated with NIV, were prospectively recruited. After data processing, the patients were divided into two groups: 1) successful NIV treatment group; 2) failed NIV treatment group. RESULTS: On admission arterial pH and Glasgow coma scale (GCS) levels were lower (pH: p < 0.05, GCS: p < 0.05), and Acute Physiology and Chronic Health Evaluation II (APACHE) score and PaCO(2) were higher (p < 0.05) in the NIV failure group. Arterial pH was lower (p < 0.05) and PaCO(2) and respiratory rate were higher (p < 0.05) after 1h, and arterial pH was lower (p < 0.05) and PaCO(2) (p < 0.05), respiratory and heart rate were higher (p < 0.05) after 4h in the NIV failure group. CONCLUSION: Measurement and monitoring of certain parameters may be of value in terms of predicting the effectiveness of NIV treatment.